PERENCANAAN SISTEM AGC (AUTOMATIC GENERATION CONTROL) PADA SISTEM TENAGA LISTRIK MULTI AREA - Irfan Rashidi; Imam Robandi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Multi area system is modified to take into account the effect of bilateral contracts on the dynamics. The concept of DISCO participation to simulate these bilateral contracts is introduced and ref'lected in two area block diagram. The AGC system is implemented into 500 KVs electric power system of Java and Bali. These result characteristic is tend good stabilization.